An case report of persistent giardiasis - Daniele Crotti; Elisabetta Antonelli; Maria Letizia D’Annibale (Microbiologia Medica, 2009)
The authors describe a persistent case of autoctonous giardiasis in an Italian adult man. Patient’s habits, clinical findings and diagnostic criteria are reported.The persistent elimination of Giardia spp. cysts with faeces along several month and years could be related to a repeated environmental ingestion or due to the onset of resistance towards the antiprotozoal drug.